Review on Role of Avagaha Sweda in Anorectal disorders (International Journal of Ayurveda and Pharma Research, 2025)
In today’s fast-paced world, environmental factors and lifestyle changes contribute to various diseases, including anorectal disorders. Swedana (sudation therapy) is primarily a Purva karma (preparatory procedure) but serves as a Pradhana Karma (main therapy) in certain conditions. Avagaha Sweda involves immersing the affected body part in a tub containing medicated liquids like Kwatha (decoctions), Taila (medicated oils), or Sneha Dravyas (unctuous substances). This therapy induces localized fomentation, which helps in pain relief, inflammation reduction, and wound healing. It is particularly beneficial in anorectal diseases such as hemorrhoids, fissures, and fistulas by improving local circulation, softening tissues, and promoting faster recovery. This review article highlights the importance, mechanism of action, and therapeutic efficacy of Avagaha Sweda in managing anorectal disorders, emphasizing its relevance in contemporary Ayurvedic practice.